2019
DOI: 10.3390/en12061097
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Output Conditional Inference Trees Applied to the Electricity Market: Variable Importance Analysis

Abstract: Predicting electricity prices and demand is a very important issue for the energy market industry. In order to improve the accuracy of any predictive model, a previous variable importance analysis is highly advised. In this paper, we propose an alternative framework to assess the variable importance in multivariate response scenarios based on the permutation importance technique, applying the Conditional inference trees algorithm and a ϕ -divergence measure. Our solution was tested in simulated examples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Five hyperparameters are used to tune the CIT algorithm [16]: ntree, mtry, M axdepth, minsplit, minbucket. [41] performed a sensitivity analysis based on the computation of Sobol indices in order to assess the importance of these hyperparameters on the accuracy of the CIT algoritm when used as base leaner for VIA. The study showed that mtry has the highest impact on the accuracy of the proposed algorithm for VIA.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five hyperparameters are used to tune the CIT algorithm [16]: ntree, mtry, M axdepth, minsplit, minbucket. [41] performed a sensitivity analysis based on the computation of Sobol indices in order to assess the importance of these hyperparameters on the accuracy of the CIT algoritm when used as base leaner for VIA. The study showed that mtry has the highest impact on the accuracy of the proposed algorithm for VIA.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Finally, the dissimilarities between the Mahalanobis distance vectors before and after permuting the predictor under assessment are quantified using the χ 2 -distance (symmetric metric). Although a similar solution was presented in [41], in this work we improve the algorithm and adapt it to the imbalanced classification problem by using the Mahalanobis instead of the Euclidean distance. This metric has been extensively ap-plied in clustering problems for outlier detection.…”
Section: Introductionmentioning
confidence: 99%